Intervenção ortográfica em escolares com e sem dificuldades de escrita - Sampaio, Maria Nobre [UNESP]; Capellini, Simone Aparecida [UNESP] (My University, 2015)
The purpose of the research reported here was to verify the effects of an intervention program in students with and without disabilities of writing. Participants were 40 students from 3 to 5 years of public elementary school, divided into two major groups: GI (20 students with difficulties in writing, subdivided into GIe and GIc) and GII (20 students without difficulties of writing, subdivided into GIIe and GIIc). In a pre- and post-testing, the groups were submitted to the Pro-Spelling. All groups, in general, presented means of hits that have become higher in post-testing, but the results also showed that GIe and GIIe showed better performance against GIc and GIIc. It was concluded that the elaborate intervention program was effective for the students in this study, indicating that it can help both teachers and clinical professionals working in education, minimizing the difficulties of students with spelling lag.
Intervention with students with spelling difficulties in writing and without difficulties
Keywords: Learning; Social intervention; Writing